2015
DOI: 10.1002/em.21931
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials and neurodegeneration

Abstract: The increasing application of nanotechnology in various industrial, environmental, and human settings raises questions surrounding the potential adverse effects induced by nanosized materials to human health, including the possible neurotoxic and neuroinflammatory properties of those substances and their capability to induce neurodegeneration. In this review, a panel of metal oxide nanoparticles (NPs), namely titanium dioxide, silicon dioxide, zinc oxide, copper oxide, iron NPs, and carbon nanotubes have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 160 publications
(214 reference statements)
0
27
0
3
Order By: Relevance
“…DNA damage induction by carbon nanotubes is well recognized. [33][34][35] In this study, we have shown that GO, a two-dimensional structure, also can induce DNA damage at a concentration of 10 μg/mL. Figure 7 D shows the semi-quantitative data of DNA damage in terms of length of genomic material (pixels).…”
Section: Methodsmentioning
confidence: 91%
“…DNA damage induction by carbon nanotubes is well recognized. [33][34][35] In this study, we have shown that GO, a two-dimensional structure, also can induce DNA damage at a concentration of 10 μg/mL. Figure 7 D shows the semi-quantitative data of DNA damage in terms of length of genomic material (pixels).…”
Section: Methodsmentioning
confidence: 91%
“…C'est le cas pour les particules inhalées comme l'amiante, la silice (Pezerat, 1989), les fumées de diesel (Ghio, 2012), les nanoparticules (Migliore, 2015). Du côté des molécules organiques, un système enzymatique occupe une place particulière, ce sont les mono-oxygénases à cytochromes P450 qui assurent la première phase du métabolisme des substances étrangères.…”
Section: Retour à Madame Bunclassified
“…Some toxicological studies have reported that the nanomaterials can be cytotoxic [387][388][389][390][391][392], genotoxic [391,[393][394][395][396][397][398][399], bactericidal [400][401][402][403][404], neurotoxic [405][406][407][408][409] and ecotoxic [410][411][412][413][414].…”
Section: Nanoecotoxicology Health Risks and Regulationsmentioning
confidence: 99%